Granting Business License to Fuel Traders “Pertamini” As a Form of Legal Protection - Nirwan Junus; Karlin Zakaria Mamu; Mohamad Syahnez W. Aditya Cono (Universitas Negeri Gorontalo, 2021)
Oil and Gas plays an important role in the fulfillment of fuel needs from both the industrial and transportation sectors. This regulation on Oil and Gas has provided a legal basis in its implementation. The presence of retail fuel businesses